Preparation, Characterization, and Antimicrobial Activities of Bimetallic Complexes of Sarcosine with Zn(II) and Sn(IV) - Yasir Arafat; Saqib Ali; Saira Shahzadi; Muhammad Shahid (Bioinorganic Chemistry and Applications)
Heterobimetallic complexes of Zn(II) and Sn(IV) with sarcosine have been synthesized at room temperature under stirring conditions by the reaction of sarcosine and zinc acetate in 2 : 1 molar ratio followed by the stepwise addition of CS2 and organotin(IV) halides, where R = Me, n-Bu, and Ph. The complexes were characterized by elemental analysis, FT-IR and NMR (1H, 13C) spectroscopy. IR data showed that the ligand acts in a bidentate manner. NMR data revealed the four coordinate geometry in solution state. In vitro antimicrobial activities data showed that complexes (3) and (4) were effective against bacterial and fungal strains with few exceptions.